Are Canada's Labour Standards Set In The Third World? Historical Trends And Future Prospects - Huberman, Michael (C.D. Howe Institute, 2005)
This framework seems to mesh with the economic history of Canada's two central provinces, Ontario and Quebec, around the mid-twentieth century. Quebec was clearly the labour-abundant province, Ontario the capital-abundant region. Many labour reforms were first introduced in Ontario because it was the wealthier region. Since the two regions remained relatively large trading partners - as they were as long as tariffs protected Canadian industry - Quebec had an incentive to match Ontario's labour standards. ( 16) Thus, as long as Canada had effective tariff protection, producers and workers in the export industries in both regions benefited from rising labour standards, while consumers all across the country suffered, a result that was clearly not in the general interest. Since there was an incentive to overprotect, Ottawa's intervention in this area did not come up against provincial antagonism. In fact, sub-national authorities would have welcomed a central authority to coordinate standards. Richard Block and Karen Roberts (2000) provide the most exhaustive study of labour standards as they were in the late 1990s. Their results show a more consistent pattern. They divide provincial, territorial and federal labour standards for 1998 into nine categories reproduced in Table 3. ( 19) Each category is itself a composite of several indicators. Thus the category "paid time off" comprises, but is not restricted to, the variables found in Table 2. The calculation of the index value for each category followed a two-step procedure. First, individual provisions or labour standards in each category were given an index value that was greater the higher the level of employee protection; secondly, each provision was given a weight to represent its importance in its category. ( 20) There is some degree of arbitrariness in all this but, given the large number of standards included in the exercise, it would be expected that errors of commission would cancel out. The first two columns of Table 4 report the sum of the index values (nine labour standards and employment insurance) and the sum of the index values after each provision was deflated by an estimate of coverage. The higher the value, the greater the degree of labour protection. The last column of Table 4 gives the ranking of labour protection of each province and territory in North America in descending order. ( 21 ) Jurisdiction Minimum wage Over-time Paid time off Worker's compensation Federal 4.28 10.00 6.27 6.77 Alberta 1.52 (12) 7.28 (7) 7.61 (2) 6.69 (10) British Columbia 7.04 (1) 10.00 (1) 6.27 (4) 8.58 (3) Manitoba 2.44 (6) 10.00 (1) 5.89 (8) 6.54 (11) New Brunswick 2.44 (6) 3.21 (12) 5.38 (11) 5.99 (12) Newfoundland 2.44 (6) 4.57 (11) 5.53 (10) 7.25 (9) North West Territories 6.12 (3) 10.00 (1) 6.27 (4) 8.82 (1) Nova Scotia 2.44 (6) 1.85 (1) 5.71 (9) 7.32 (8) Ontario 6.12 (3) 7.28 (7) 6.07 (7) 7.64 (7) Prince Edward Island 2.44 (6) 5.92 (10) 5.20 (12) 7.72 (6) Quebec 6.12 (3) 7.28 (7) 7.23 (3) 8.35 (5) Saskatchewan 2.44 (6) 10.00 (1) 9.11 (1) 8.66 (2) Yukon 7.04 (1) 10.00 (1) 6.27 (4) 8.43 (4) Jurisdiction Collective Employment Unjust Occupational Advance notice bargaining equity discharge safety of plant closing and health largescale layoffs Federal 6.00 9.00 7.00 4.33 5.53 Alberta 6.00 (9) 8.10 (11) 7.00 3.07 (5) 0.00 (11) British Columbia 10.00 (1) 8.60 (5) 7.00 3.20 (2) 7.89 (1) Manitoba 9.00 (3) 9.10 (1) 7.00 3.13 (4) 6.03 (5) New Brunswick 8.00 (8) 8.10 (11) 7.00 2.11 (10) 5.71 (6) Newfoundland 9.00 (3) 8.60 (5) 7.00 2.08 (11) 5.03 (8) North West Territories 6.00 (9) 9.00 (3) 7.00 2.18 (8) 3.21 (10) Nova Scotia 6.00 (9) 9.10 (1) 7.00 2.18 (8) 6.37 (4) Ontario 9.00 (3) 8.50 (9) 7.00 3.24 (1) 7.03 (2) Prince Edward Island 9.00 (3) 8.60 (5) 7.00 1.87 (12) 0.00 (11) Quebec 10.00 (1) 9.00 (3) 7.00 2.63 (7) 4.50 (9) Saskatchewan 9.00 (3) 8.60 (5) 7.00 3.00 (6) 6.87 (3) Yukon 6.00 (9) 8.50 (9) 7.00 3.17 (3) 5.21 (7)
Keywords: Canada; Economic history; Jurisdiction; Labour; Labour law; Ontario; Quebec; Tariff; Unemployment benefits